Alcohol Use Cravings as a Mediator Between Associated Risk Factors on Increased Alcohol Use among Youth Adults in New York During the COVID-19 Pandemic. Issue 4 (2nd October 2021) - Opara, Ijeoma; Malik, Sana; Lardier, David T.; Gamble-George, Joyonna; Kelly, Ryan J.; Okafor, Chukwuemeka N.; Greene, R. Neil; Parisi, Deanna
ABSTRACT: The sudden increase in alcohol use in the young-adult population during the COVID-19 pandemic may be partially explained by social isolation and stress due to restricted stay-at-home orders. The goal of this study was to assess specific psychological factors (e.g., anxiety, depressive symptoms, sleep disturbances, and alcohol cravings) and COVID-19 diagnoses and their association with increased alcohol use and misuse during the COVID-19 pandemic among New York residents ages 18–35 years. Survey data were collected via Qualtrics between July 2020 and October 2020. Path analysis tests were employed to test alcohol-use cravings as a mediator. Among the total sample ( N = 575), the mean age was 27.94 ± 4.12; a majority of the participants were White non-Hispanic (66%), female (55%), and had completed a four-year college or university degree ( n = 249; 43.5%). Results revealed that alcohol-use cravings was a significant mediator between sleep disturbances, having a COVID-19 diagnoses, and having mental-health symptoms on increased alcohol use. Our findings underscore the importance of providing resources for alcohol-use prevention and treatment in this unprecedented COVID-19 era. Policymakers, public-health professionals, and clinicians have a significant role in curbing the COVID-19-induced substance-use epidemic.